The Influence of Switching Barriers and Customer Service on Customer Satisfaction at Hotel Harris Kelapa Gading with Perceived Quality as Moderator - Lukiyana Lukiyana; Muhammad Junaid Kamaruddin; Muhammad Herdi Firmansyah (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine how switching barriers and customer service influence customer satisfaction, while also testing whether perceived quality moderates (strengthens or weakens) these relationships. The study is positioned within the context of increasingly intense competition in service industries, where retaining customers and ensuring satisfaction are critical for long-term sustainability and loyalty. Methodology/approach: Quantitative approach using questionnaire data from 114 customers across various service sectors. Data analysis applies multiple regression to test direct effects and moderation analysis to test the moderating role of perceived quality. Results/findings: The findings suggest that switching barriers and customer service significantly enhance customer satisfaction. Financial, procedural, and relational barriers reduce the intention to switch, fostering continued engagement when service meets expectations. Additionally, perceived quality serves as a crucial moderating factor, strengthening the effect of switching barriers and customer service on satisfaction, with stronger relationships when customers perceive high overall service quality. Conslusion: Customer satisfaction in service industries can be improved through effective management of switching barriers and enhanced customer service quality, particularly when customers perceive the overall service quality as high. Limitations: The study uses a relatively small sample (114 respondents) and relies on self-reported survey data, which may limit generalizability across all service industries and contexts. Contribution: Provides empirical insights for service businesses on how to increase customer satisfaction and loyalty by improving customer service, strategically managing switching barriers, and enhancing perceived quality as a key reinforcing factor.